Evaluation of Immunization Coverage in the Adult Population of Canada - Philippe Duclos (Canadian Journal of Infectious Diseases)
The immunization coverage of the adult population, availability of records and knowledge of proper schedules were assessed using the Canada Omnibus Survey, a door to door survey of a modified probability sample conducted four times a year. In total, 8021 interviews were completed over four periods. Only 43% of individuals 65 years of age or older reported receiving a dose of influenza vaccine during the year preceding the interview. Twenty-one per cent (38% of those under 25 and 9% of those 65 and older) reported having an immunization booklet at home. Twelve per cent believed that there were no vaccines that they should be receiving regularly. Only 61% of those who believed they should receive some shots regularly knew when the next one was due. Overall, 48% felt they had enough information about the vaccines they should receive. This information will help target immunization programs for the adult population.